Analysis of spatio-temporal structure of EEG-activity to form an objective assessment of the individual characteristics of the sleep-wake behavior - A. A. Putilov; O. G. Donskaya; Ye. G. Veryovkin; D. A. Putilov (Бюллетень сибирской медицины)
The structure of individual variation in waking EEG was elaborated in 130 sleep deprived subjects. Its quantitative relationship with chronotype (morning and evening lateness), somnotype (daytime and anytime sleepability) and trototype (daytime and anytime wakeability) was described. The findings indicate that individual vulnerability of wakeability to sleep loss can serve as a quantitative predictor using the structures of waking EEG at daytime and during sleep deprivation.